03 Varicose and non-varicose veins are able to activate the hypoxia-inducible factor pathway when exposed to hypoxia. Issue 24 (24th November 2011) - Lim, C S; Kiriakidis, S; Paleolog, E; Davies, A H
Abstract : Introduction: Hypoxia has been postulated to contribute to various venous pathology including varicose veins (VV) and vein graft thrombosis or stenosis. Hypoxia-inducible factors (HIF) are nuclear transcriptional factors regulating transcription of genes mediating oxygen homoeostasis. This study aimed to investigate the in vitro effects of hypoxia on the HIF pathway in VV and non-varicose veins (NVV). Methods: Six VV and six NVV were used to prepare organ cultures which were exposed to normoxia, hypoxia (oxygen 1%), or hypoxia-mimicking dimethyloxallyl glycine (DMOG) 1 mM for 16 h. The veins were analysed for HIF-1α, HIF-2α, and their target genes expression with Q-PCR and immunoblot. Results: Hypoxia and DMOG treatment was associated with a significant reduction of HIF-1α mRNA expression in VV (0.48±0.11; p<0.05 and 0.24±0.07; p<0.001, respectively) and NVV (0.39±0.06; p<0.001 and 0.23±0.04; p<0.001, respectively) compared to normoxia. No significant HIF-2α mRNA expression change was measured in both veins in hypoxia or DMOG compared to normoxia. Increased HIF-1α and HIF-2α protein expression was observed in VV and NVV in hypoxia or DMOG compared to normoxia. Significant increases of HIF target genes (CA9, BNIP-3, GLUT-1, PHD-2 and PHD-3) mRNA expression were measured in VV and NVV in hypoxia or DMOG compared to normoxia. The upregulation of HIF target genes was also reflected at protein level. Conclusion: Exposure of VV and NVV to hypoxia or DMOG was associated with upregulation of HIF-1α and HIF-2α protein, and HIF target genes. Our data suggest that the HIF pathway may play a role in hypoxia related venous pathology.